2017
DOI: 10.1016/j.mimet.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Silkworm larvae plasma (SLP) assay for detection of bacteria: False positives secondary to inflammation in vivo

Abstract: The silkworm larvae plasma (SLP) assay has been developed as a means to detect bacterial peptidoglycan as a surrogate for live bacteria. Here, we present results that indicate that generation of melanin by this assay is not fully reliable as a surrogate marker for bacterial count.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…administration. Ma et al [19] also reported rapid clearance of gDNA from both live and inactivated Lp.…”
Section: Results and Dicussionmentioning
confidence: 94%
See 1 more Smart Citation
“…administration. Ma et al [19] also reported rapid clearance of gDNA from both live and inactivated Lp.…”
Section: Results and Dicussionmentioning
confidence: 94%
“…Detection of Lp genomic (g)DNA in lung tissue was performed as described [19]. Lungs from mice inoculated with Lp were stored at 280°C in RNAlater (Thermo Fisher Scientific); gDNA was isolated and evaluated on an ABI 7500 Real Time PCR system (Thermo Fisher Scientific), with primers and probe designed to detect the Lp 16s-23s intergenic region as described [20], including forward primer, 59-TGG ATC ACC TCC TTT CTA AGG AAT-39; reverse primer, 59-TGT TCT CGG TTT CAT TAT GAA AAA ATA-39; and probe, 59-ACA TTC TTC GAA ACT TTG T-39-MGB and calibrated via interpolation to standard curves.…”
Section: Detection Of Lp Genomic Dnamentioning
confidence: 99%
“…For example, in the above-mentioned study by Zhiping et al [14], the exposure to peptidoglycans was assessed using a muramic acid as its marker. Also, recent reports suggest that the SLP test should be used with caution as it can give the "false-positive results" contributing to overestimation of the real exposure [30].…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy could however be due to differences in PGN reactivity. The SLP reagent was indeed reported to react with free PGN, but also with trace of living or inactivated bacteria [29] , [38] . In contrast, the size of PGN fragments was shown to determine the responses triggered by inflammatory cells in human and animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, PGN detection in icodextrin batches is difficult, because of its relatively low concentration by comparison with the icodextrin itself, which behaved as an interfering substance. Moreover, routine monitoring for PGN with SLP assay has some shortcomings, because of limitation in the detection [38] and cross-reactivity with other substances, such like β1-3 glucans [29] . In the light of needs for other tests, we decided to compare the efficacy of different bio-assays to detect bacterial contamination in glucose polymer samples.…”
Section: Discussionmentioning
confidence: 99%